Development Of A Portable Membrane-Color-Sensor For Detection Of Heavy Metal - Azmi, Nur Atiah (2019)
A basic requirement of colorimetric membrane-based sensors is to allow the target analyte to access to the chromophore while retaining a strong chromophore immobilization on the membrane surface. This study elucidates the fundamental perceptive of membrane morphologies and their influences on the binding of chromophores to detect aqueous heavy metals ions. Flat sheet membranes consist of mixed polymer cellulose acetate (CA) and chitosan (CS) was acts as the sensing platform for chromophore binding. Membrane with 17 wt.% CA and 1 wt.% CS showed to have the high binding capacity and high binding stability up to 90 days of measurement. The addition of deionized water (DI) as the non-solvent additive has also shown to improve the membrane porousness, which improved the sensor’s sensitivity. Visible color changes of the colorimetric membrane from blue-greenish to peachy-pink was observed when it was in contact with the Pb2+ ions in 1 ppm Pb(NO3)2. Selection of sensitive chromophore (Dithizone, 1-(2-pyridylazo) 2-naphthol and 4-(2-pyridylazo)-resorcinol) and its immobilization strategy on the membrane sensor has also been carried out. Dithizone (DTz) at unadjusted pH was capable to produce an obvious color transition observed through UV-visible absorption spectrum and naked eyes recognition. The optimum immobilization of DTz required the concentration of 100 ppm and 10 minutes immobilization time. To determine the sensitivity and selectivity of the developed colorimetric sensor in the single and mixed aqueous heavy metals ions solution, the sensing conditions such as pH, type of heavy metals (Pb2+, Hg2+, Zn2+ and Cu2+), concentration and response time were evaluated. The developed DTz-membrane sensor in this work has exhibited quick (within 1 minute) color change and was able to display distinctive color changes from blue-greenish to peachy-pink, yellowish-orange, red-violet and reddish-brown in the response to the presence of Pb2+, Hg2+, Zn2+ and Cu2+ in aqueous solutions. The quantitative analysis using RGB (R:Red; G:Green; B:Blue) data showed that each tested metal ions have demonstrated their own RGB’s recognition pattern phase without significant interfering effects among the heavy metal ions. This showed the potential for practical applications of on-site quick detection on either single or mixed heavy metal ions. The DTz-CA/CS membrane showed a distinctive color changed in the detection of synthetic heavy metals ions in the water that obtain from Kerian River. The synthetic heavy metals ions was prepared the at maximum permissible limit of 0.1 ppm Pb2+, 2.0 ppm Zn2+ and 0.2 ppm Cu2+ for industrial effluent (Standard A) by Malaysian Department of Environment. This membrane sensor was successfully applied for the determination of heavy metals ions not only limited to river water quality assessment but also included the cosmetic product analysis (lipstick samples) at the low trace level of heavy metals ions.